2022
DOI: 10.3390/agronomy12040843
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Characteristics of Dryness/Wetness in the Wine Regions of China from 1981 to 2015

Abstract: China has a marked continental monsoon climate characterized by dry and wet hazards that have destructive impacts on grape yields and quality. The purpose of this study was to analyze the spatiotemporal characteristics of dryness/wetness in the wine regions of China and explore the links between these variations and large-scale climatic factors. The crop-specific standardized precipitation evapotranspiration index (SPEI) was used to characterize the dryness/wetness using meteorological data collected at 168 me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 53 publications
(85 reference statements)
0
1
0
Order By: Relevance
“…The study found that the Hexi Corridor, one of China's major wine producing regions, is experiencing severe drought. (Yang et al, 2022). In recent years, with the aggravation of global climate change and freshwater shortage, soil water availability in agricultural production has been greatly affected (Gu et al, 2019; Xu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The study found that the Hexi Corridor, one of China's major wine producing regions, is experiencing severe drought. (Yang et al, 2022). In recent years, with the aggravation of global climate change and freshwater shortage, soil water availability in agricultural production has been greatly affected (Gu et al, 2019; Xu et al, 2011).…”
Section: Introductionmentioning
confidence: 99%